Історія становлення та розвитку волонтерства в Україні - Сіньова, Людмила Миколаївна (My University, 2023)
History of the formation and development of volunteering In UkraineThe article is devoted to the study of the evolution of the volunteer movement. In particular, the article analyzes volunteering from the appearance in the international arena to the introduction into the national legal system. The whole spectrum of volunteer activity, which aims to help others, is considered. In accordance with the above examples, it was concluded that volunteering is a necessary and socially useful activity.

Стаття присвячена дослідженню еволюції волонтерського руху. Зокрема, в статті проаналізовано волонтерство від появи на міжнародній арені до впровадження в національну правову систему. Розглянуто весь спектр волонтерської діяльності, яка має за мету допомогти іншим. Відповідно до наведених прикладів зроблено висновок, що волонтерство є необхідною та суспільно корисною діяльністю.
Keywords: волонтерство; благодійна діяльність; волонтерські організації; volunteering; charity; civil society; volunteer organizations